2016
DOI: 10.1103/physrevapplied.6.054019
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Imaging Using a Disordered Cavity with a Dynamically Tunable Impedance Surface

Abstract: We perform microwave imaging using a dynamically reconfigurable aperture based on a tunable, disordered cavity. The electrically-large cavity is cubic, with a spherical-deformation, and supports a multitude of distinct electromagnetic modes that vary as a function of excitation frequency. With a set of irises introduced into one wall of the cavity, the cavity modes couple to spatially-distinct radiative modes that vary as a function of the driving frequency. To increase the diversity of the radiated fields, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 62 publications
1
74
0
Order By: Relevance
“…It should be noted that the SVD has long been used for image inversion and information theoretic techniques [35,38,66,74,75]. Recent applications have studied system resolution based on the SVD [74] and have also studied how many independent measurements can be taken in an imaging system [35,38,66,75]. More commonly, the SVD has been used to invert matrix equation (5) and directly solve forσ in the inverse scattering problem [66].…”
Section: Image Reconstructionmentioning
confidence: 99%
“…It should be noted that the SVD has long been used for image inversion and information theoretic techniques [35,38,66,74,75]. Recent applications have studied system resolution based on the SVD [74] and have also studied how many independent measurements can be taken in an imaging system [35,38,66,75]. More commonly, the SVD has been used to invert matrix equation (5) and directly solve forσ in the inverse scattering problem [66].…”
Section: Image Reconstructionmentioning
confidence: 99%
“…According to Reference [9], in order to reduce the mutual coherences, an interesting option is to construct the modes as independent and identically distributed as random variables. Thus various antenna structures have been proposed for MCI by intuitively randomizing resonant cavity structures or element resonant properties, such as mode-mixing cavity [10], printed aperiodic cavity with irises distributed in a Fibonacci pattern [11], disordered cavity with dynamically tuneable impedance source [12] and printed metasurface with subwavelength metallic cylinders in the cavity [13]. These antennas have shown that the mutual coherences in the measurement matrix can be effectively reduced by introducing disorder and randomness in the antenna structures.…”
Section: Introductionmentioning
confidence: 99%
“…The metasurface design can be upgraded, for instance, for linear phase control with a varactor-populated mushroom-structure as in Ref. [39]. The cavity constitutes a very stable enclosure that is completely shielded from the outside.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The reflections off the irregular cavity walls interfere and give rise to a speckle-like wave field [35], very much like scattering events in multiply scattering optical media such as thin paint layers or biological tissue [21,36]. Furthermore, complex microwave cavities are leveraged in fundamental research on quantum chaos [37] as well as in applications ranging from security screening [38,39] and biomedical imaging [40], via sensing [41,42] and wireless power transfer [43][44][45][46] to electromagnetic compatibility tests [47].…”
Section: Demonstration With Indoor Wireless Communication Signalsmentioning
confidence: 99%